Cationic liposome- multi-walled carbon nanotubes hybrids for dual siPLK1 and doxorubicin delivery in vitro - Pereira, Sara; Lee, Jin; Rubio, Noelia; Hassan, Hatem A. F. M.; Mohamed Suffian, Izzat Fahimuddin; Wang, Julie Tzu-Wen; Klippstein, Rebecca; Ballesteros, Belén; Al-Jamal, Wafa; Al-Jamal, Khuloud (Springer US, 2015)
PURPOSE: To formulate f-MWNTs-cationic liposome hybrids for the simultaneous delivery of siPLK1 and doxorubicin to cancer cells. METHOD: f-MWNTs-cationic liposome hybrids were prepared by the thin film hydration method where the lipid film was hydrated with 100 μg/ml or 1 mg/ml of ox-MWNTs-NH3 (+) or MWNTs-NH3 (+) in 5% dextrose. siRNA complexation and protection ability was determined by agarose gel electrophoresis. f-MWNTs and liposome interaction was evaluated using Nile Red (NR) fluorescence spectroscopy. Cellular uptake in A549 cells was assessed by flow cytometry. Silencing of target proteins was determined by Luciferase and MTT assays. Sub-G1 analysis was performed to evaluate apoptosis following co-delivery of siPLK1 and Doxorubicin (Dox). RESULTS: Zeta potential and siRNA complexation profile obtained for all hybrids were comparable to those achieved with cationic liposomes. ox-MWNTs-NH3 (+) showed greater extent of interaction with cationic liposomes compared to MWNTs-NH3 (+). ox-MWNTs-NH3 (+) was able to protect siRNA from nuclease-mediated degradation. Enhanced cellular uptake of both the carrier and loaded siRNA in A549 cell, were observed for this hybrid compared to the liposomal carrier. A synergistic pro-apoptotic effect was obtained when siPLK1 silencing was combined with doxorubicin treatment for the hybrid:siRNA complexes compared to the lipoplexes, in A549 cells in vitro. CONCLUSIONS: f-MWNTs-cationic liposome hybrid designed in this study can serve as a potential vehicle for the co-delivery of siRNA and cytotoxic drugs to cancer cells in vitro.